DMARDs, Biologic Agents and Novel Experimental Strategies in The Treatment of Rheumatoid Arthritis - Sagrika Kukade; Shilpa S. Borkar; Pankaj Dhapake; Jagdish R. Baheti (Emerging Trends in Personalized Medicines, 2024)
An inflammatory and autoimmune disease, rheumatoid arthritis (RA) causes severe pain and inflammation in affected areas of the body. According to the report, there is no known cure for RA. Therefore, reducing discomfort and halting future harm must be the goals of present therapy. For the purpose of prevention and to reduce disease activity in RA patients, significant success has been achieved with the continued development of disease-modifying antirheumatic drugs (DMARDs). The inflammatory synovial joints that characterise rheumatoid arthritis (RA), a chronic autoimmune illness, cause joint degradation, incapacity, and a reduction in quality of life. Treatment for RA has advanced significantly over the years, especially with the advent of biologic medicines, disease-modifying anti-rheumatic medications (DMARDs), and creative experimental approaches. Unfortunately, some patients continue to respond poorly to DMARDs, thus it is necessary to develop new targets and treatments in treatment of RA. The foundation of RA treatment is the use of DMARDs, with methotrexate being the most effective option. Due to their ability to specifically target immune system components implicated in the pathophysiology of RA, biologic medicines have completely changed the way that the illness is managed. Clinical outcomes and disease activity have been demonstrated to be significantly improved by tumour necrosis factor (TNF) inhibitors, such as adalimumab and etanercept. The therapy arsenal has also been augmented by additional biologics that target B cells, T cells, and interleukin-6 (IL-6), giving patients who are not responsive to or tolerate traditional therapies more options. These medications delay the progression of illness and maintain joint function by lowering inflammation and inhibiting the immune system. But some patients may not react well to conventional DMARDs, thus other treatment alternatives must be investigated. Finding potential therapeutic targets and methods could be made easier by comprehending the pathogenetic roles played by the various molecules in RA. With a focus on the mechanisms that cause inflammation and the creation of new drugs for blocking the various modulators in RA, this review discusses both existing and emerging targets, including proteins.
Keywords: DMARDs; Novel Strategies; Protein Targets; rheumatoid arthritis; treatment